The aquatic entomology collection in the Zoological Museum at the University of Costa Rica: updated checklist of genera, importance, and future challenges. - Springer, Monika (Revista de Biología Tropical, 2019)
Aquatic macroinvertebrates, and especially insects, are the group of organisms most commonly used to determine the health of ecosystems in water quality studies and freshwater biomonitoring. The most important scientific collection of this group in Costa Rica is located in the Zoological Museum of the University of Costa Rica (MZUCR) and includes material from scientific research, thesis and student projects, as well as samples from environmental studies and aquatic monitoring by consultants and institutions. In this work, an updated list of the collection’s material is presented, which includes 98 families and 341 identified taxa (genera, tribes or subfamilies) from eleven insect orders, with Coleoptera and Diptera as the most taxonomical diverse orders. Studies which resulted from revisions of the collection material are cited, including new species, genera, and family records, as well as descriptions of new species and associations of immature stages with their adults. The main challenges for this collection include the taxonomic identification of certain groups, keeping up with the constant collection growth and updating the associated database.